First record of predation on the bat Carollia perspicillata by the false coral snake Oxyrhopus petolarius in the Atlantic Rainforest - Frederico Gustavo Rodrigues França; Rafaella Amorim de Lima (Biotemas, 2012)
Records of bats as prey of snakes are very few in the literature, but recent studies have shown that this predation doesn’t seem to be an unusual phenomenon. We present here the first record of predation on the bat Carollia perspicillata by the false coral snake Oxyrhopus petolarius in an Atlantic Rainforest area in the Northeastern Brazil.